Numerical analysis of cocurrent conical and cylindrical axial cyclone separators - Nor, M.A.M. (Institute of Physics Publishing, 2015)
Axial concurrent liquid-liquid separator is seen as an alternative unit to the traditional tangential counter current cyclone due to lower droplet break ups, turbulence and pressure drop. This paper presents the numerical analysis of a new conical axial cocurrent design along with a comparison to the cylindrical axial cocurrent type. The simulation was carried out using CFD technique in ANSYS-FLUENT software. The simulation results were validated by comparison with experimental data from literature, and mesh independency and quality were performed. The analysis indicates that the conical version achieves better separation performance compared to the cylindrical type. Simulation results indicate tangential velocity with 8 higher and axial velocity with 80 lower recirculation compared to the cylindrical type. Also, the flow visualization counters shows smaller recirculation region relative to the cylindrical unit. The proposed conical design seems more efficient and suits the crude/water separation in O&G industry.